Wicked game of smart specialization : a player’s handbook - Lundström, Niklas; Mäenpää, Antti (Taylor & Francis, 2017)
The objective of this article is to explore the theoretical foundations of a wicked game. The theoretical part is based on the notion of wicked problems, which is developed further. It is also illustrated that the latest innovation strategy of the European Union, called smart specialization, resembles a wicked game. Comparison between the two revealed several similarities gives new insights into the theory of wicked problems and into the process of smart specialization.
Keywords: wicked problems; wicked games; smart specialization; regional development policy; regional innovation; fi=Aluetiede|en=Regional Studies|